PENGARUH 2,4-D DAN BA TERHADAPINDUKSIKALUS EMBRIOGENIK PADA KULTUR MERISTEM JAHE {Zingiber officinale Rose.) - Rama Riana Sitinjak; Otih Rostiana; Karyono Karyono; Titin Supriatun (BERITA BIOLOGI, 2006)
The aim of this study was to evaluate the effects of 2,4-dichlorophenoxyacetic acid (2,4-D) and N -benzyladenin (BA) to embryogenic callus induction of meristem culture in ginger {Zingiber officinale Rose). Completely Randomixed Design was applied using factorial pattern, replicated 3 times. Two factors were assigned i.e: 2,4-D (1.0, 2.0 and 3.0 mg/L) and BA (0.0, 1.0, 3.0 and 5.0 mg/L). Result showed that 2,4-D and BA significantly affected the embryogenic callus induction. The highest embryogenic callus (93.33%) was achieved on MS (Murashige & Skoog) containing combination of 1.0 mg/L 2,4-D and 3.0 mg/L BA, after 8weeks incubation.Histological evaluation informed that the incubation of embryogenic calli started from cortex cells adjacent the meristem vascular tissues.